1996
DOI: 10.1177/144078339603200109
|View full text |Cite
|
Sign up to set email alerts
|

Drought, discourse, and Durkheim: a research note

Abstract: In this paper we report the results of an extensive qualitative analysis of Australian discourses on drought. Themes in Australian discourses on drought are broadly Durkheimian in nature, referring to the need to reaffirm social morality and solidarity in the face of an unexpected and unprecedented challenge from nature. A brief analysis of statistical data suggests that drought discourses have a relative autonomy from both meteorological and social structural determinants. The paper concludes by theorising wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Recent empirical research in sociology has found cultural discourse approaches to be quite effective at developing unique analyses of varied social phenomenon (Alexander 2003;Alexander and Smith 1993;Edles 1998;Jacobs 1996Jacobs , 1998Kane 1997;Magnuson 1997;Rabinovitch 2001;Smith 1994Smith , 1998aWagner-Pacifici 1994;West and Smith 1996). I take as my specific jumping off place the work on the discourse of American civil society, begun by Alexander (1992) and Alexander and Smith (1993).…”
Section: Cultural Discourse Analysismentioning
confidence: 98%
“…Recent empirical research in sociology has found cultural discourse approaches to be quite effective at developing unique analyses of varied social phenomenon (Alexander 2003;Alexander and Smith 1993;Edles 1998;Jacobs 1996Jacobs , 1998Kane 1997;Magnuson 1997;Rabinovitch 2001;Smith 1994Smith , 1998aWagner-Pacifici 1994;West and Smith 1996). I take as my specific jumping off place the work on the discourse of American civil society, begun by Alexander (1992) and Alexander and Smith (1993).…”
Section: Cultural Discourse Analysismentioning
confidence: 98%
“…An analysis of hundreds of Australian media articles, parliamentary speeches, books, poetry and films suggested that drought was regularly invoked as a symbolic threat to the Australian national community (West and Smith 1996). Furthermore, this symbolic use of drought showed no sign of waning, despite the declining relative importance of agriculture to the national economy.…”
Section: Viewing Drought As a Symbolic Threat To The Australian Commumentioning
confidence: 99%
“…At the time, he was criticised by the media for a callous comment. An indignant opposition senator claimed he was 'condemned all over Australia by every person in the rural community for saying that drought is a natural recurring phenomenon' (Senator Brownhill cited in West and Smith 1996). Although this was partly party politics, when a policy economist asks a farmer to consider drought as a normal recurring business risk, some interpret this as asking farmers to take the enlarged metaphor of rural suffering as a normal and recurring risk.…”
Section: Viewing Drought As a Risk To The Welfare Of Rural Families Amentioning
confidence: 99%
“…West and Smith explore this idea and suggest that drought discourses respond to "symbolic and cultural needs". 59 They point to the fact that: "Notwithstanding the lessons that nature has taught us, droughts are consistently defined as unexpectedly severe in their intensity or duration". 60 Anderson's attempts to frame the 2002 drought as somehow particularly cruel because it followed a good run, as opposed to the 1990s drought which came after a rural recession and high interest rates, supports this position.…”
Section: The Politics Of Droughtmentioning
confidence: 99%